Prognostic Value of Microvascular Density in Dukes A and B (T1–T4, N0, M0) Colorectal Carcinomas - Rafael Uribarrena A; Javier Ortego; Javier Fuentes; Nuria Raventós; Pilar Parra; Rafael Uribarrena E (Gastroenterology Research and Practice)
Background. Aproximatelly 30% of patients operated on for colorectal cancer (CRC), with an expectedly favourable prognosis (Dukes A-B/T1–T4, N0, M0) suffer recurrence and/or die. Method. In order to determine if tumor microvascular density (MVD) is a prognostic factor in CRC, samples from tumors of 104 Dukes A-B CRC patients were retrospectively studied. Immunohistochemistry was performed for anti-CD34 antibody to visualize tumor vascularisation. MVD was expressed as the total number of vessels and as the percentage of microvascular area. We calculated MVD with a morphometry program and performed descriptive, bivariate, and survival statistics. Results. The mean number of vessels was 37.37/200x field, and the mean vascular area was the 3.972%. 30% of the patients with <37 vessels/field, and 21% of the patients with >37 vessels/field, experienced recurrence/death. The 35% of patients with <4% of vascular area died following recurrence, compared with 14% of patients with ≥4% of vascular area. These differences in % of vascular area were statistically significant. Conclusion. MVD expressed as the total number of vessels had no a statistically significant influence on the evolution of CRC. However, neoplasias with a greater % of vascular were associated to a better outcome.